2018
DOI: 10.1007/s12035-018-1354-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunosignature Analysis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS)

Abstract: A random-sequence peptide microarray can interrogate serum antibodies in a broad, unbiased fashion to generate disease-specific immunosignatures. This approach has been applied to cancer detection, diagnosis of infections, and interrogation of vaccine response. We hypothesized that there is an immunosignature specific to ME/CFS and that this could aid in the diagnosis. We studied two subject groups meeting the Canadian Consensus Definition of ME/CFS. ME/CFS ( n = 25) and matched control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Currently, there is no diagnostic test or validated biomarker for ME/CFS available (2,80), although some results give hope for a future diagnostic biomarker or the use of an immunosignature assay (13,(81)(82)(83)(84)(85) (20).…”
Section: Diagnosismentioning
confidence: 99%
“…Currently, there is no diagnostic test or validated biomarker for ME/CFS available (2,80), although some results give hope for a future diagnostic biomarker or the use of an immunosignature assay (13,(81)(82)(83)(84)(85) (20).…”
Section: Diagnosismentioning
confidence: 99%
“…To date, two phase 3 clinical trials have been performed for CFS using the following medications: 1) a monoclonal anti-CD20 antibody, Rituximab, and 2) the nucleic acid compounds, Rintatolimod. Both of these therapies, however, did not provide more credible evidence of efficacy than the placebo (Strayer et al, 2012; Smith et al, 2014; Günther et al, 2019). These disappointing results demand the additional trials for the development of an effective therapy for CFS.…”
Section: Introductionmentioning
confidence: 94%
“…CFS patients also had a significantly higher level of IL-8 and a lower level of IL-23. Several investigators hypothesized an immune signature could be detected by antibody profiling in ME/CFS patients [ 63 , 64 ]. Few studies showed that in most cases with ME/CFS, especially in the early stages of the disease, T cells and cytokines levels are higher than the control group [ 61 , 65 ], which could be the hallmark of CFS.…”
Section: What Causes Post-infectious Fatigue Syndromes and Me/cfs In Covid19 Patients?mentioning
confidence: 99%